IMPLEMENTASI METODE WAFA DALAM MENINGKATKAN KEMAMPUAN BACAAN DAN HAFALAN AL-QUR’AN - rahman, arif (Institut Agama Islam Negeri (IAIN) Palopo, 2024)
This thesis discusses the implementation of the Wafa method in improving students' ability to read and memorize the Qur'an: To describe and analyze the implementation of the Wafa method in learning the Qur'an at SMPIT Insan Madani Palopo ; Analyzing the impact of the Wafa method on students' ability to read and memorize the Al-Qur'an; Describe efforts to optimize the Wafa method in improving students' ability to read and memorize the Al-Qur'an. This type of research is a qualitative approach. Data sources consist of two types: primary data obtained from interviews with school principals, teachers and students at SMPIT Insan Madani Palopo and secondary data consisting of school documents, teacher documents, theoretical reviews and scientific works. Research instruments include interview guidelines, observation and documentation. Data analysis involves data reduction, data presentation and drawing conclusions. Research Findings: The implementation of the wafa method highlights a holistic approach in learning the Al-Qur'an. From group division based on ability level, the classical imitative reading learning model, implementing learning using the 5P method, to standardized wafa assessments, this method allows adaptation to students' backgrounds, leading to deeper understanding. The application of the wafa method has had a significant impact on students' abilities. From the introduction of contextual hijaiyah letters to improvements in reading with good recitation, as well as achievements in memorizing the Al-Qur'an, this method plays a crucial role in deepening students' understanding of the Al-Qur'an. Optimization steps taken include teacher qualification and training, additional guidance for students, Qur'an mukhayyam, as well as reward giving strategies to improve the quality of learning